PURCHASE DECISIONS IN ECOMMERCE: IMPACT FROM INFLUENCER AND CONTENT MARKETING - Mochamad Malik Akbar Rohandi; Putri Fariska (UPT Publikasi Ilmiah UNISBA, 2025)
Technological developments necessitate that entrepreneurs continuously adapt, particularly in the context of today’s emerging e-commerce landscape. This study aims to assess the impact of influencer marketing and content marketing on purchasing decisions in e-commerce. Employing quantitative research methods, the study seeks to generalize its findings through descriptive and verification research types. The population consists of Generation Z, with non-probability purposive sampling utilized for this research, Coefficient of Determination and anova test. The results indicate that, when considered together, both influencer marketing and content marketing have a positive and significant effect on purchasing decisions in e-commerce.